Identifying Successful Practices to Overcome Access to Care Challenges in Community Health Centers: A "Positive Deviance" Approach. (27th February 2018) - Toscos, Tammy; Carpenter, Maria; Flanagan, Mindy; Kunjan, Kislaya; Doebbeling, Bradley N.
Background: Despite health care access challenges among underserved populations, patients, providers, and staff at community health clinics (CHCs) have developed practices to overcome limited access. These "positive deviant" practices translate into organizational policies to improve health care access and patient experience. Objective: To identify effective practices to improve access to health care for low-income, uninsured or underinsured, and minority adults and their families. Participants: Seven CHC systems, involving over 40 clinics, distributed across one midwestern state in the United States. Methods: Ninety-two key informants, comprised of CHC patients (42%) and clinic staff (53%), participated in semi-structured interviews. Interview transcripts were subjected to thematic analysis to identify patient-centered solutions for managing access challenges to primary care for underserved populations. Transcripts were coded using qualitative analytic software. Results: Practices to improve access to care included addressing illiteracy and low health literacy, identifying cost-effective resources, expanding care offerings, enhancing the patient–provider relationship, and cultivating a culture of teamwork and customer service. Helping patients find the least expensive options for transportation, insurance, and medication was the most compelling patient-centered strategy. Appointment reminders and confirmation of patient plans for transportation to appointments reduced no-show rates. Conclusion: We identified nearly 35 practices for improving health care access. These were all patient-centric, uncovered by both clinic staff and patients who had successfully navigated the health care system to improve access.